2009
DOI: 10.1007/s00125-009-1324-9
|View full text |Cite
|
Sign up to set email alerts
|

Agreement among type 2 diabetes linkage studies but a poor correlation with results from genome-wide association studies

Abstract: Aims/hypothesis Little of the genetic basis for type 2 diabetes has been explained, despite numerous genetic linkage studies and the discovery of multiple genes in genome-wide association (GWA) studies. To begin to resolve the genetic component of this disease, we searched for sites at which genetic results had been corroborated in different studies, in the expectation that replication among studies should direct us to the genomic locations of causative genes with more confidence than the results of individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 129 publications
(71 reference statements)
1
16
0
Order By: Relevance
“…However, in linkage analysis the assumption is that the region segregates with disease, thus if there are multiple causal variants segregating, evidence of linkage will be present but not evidence of association. Previous studies have failed to find strong relationships between linkage peaks and association peaks [10]. Others have speculated that linkage peaks results from multiple variants [41], [45], [46], [47]; our analysis supports this.…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…However, in linkage analysis the assumption is that the region segregates with disease, thus if there are multiple causal variants segregating, evidence of linkage will be present but not evidence of association. Previous studies have failed to find strong relationships between linkage peaks and association peaks [10]. Others have speculated that linkage peaks results from multiple variants [41], [45], [46], [47]; our analysis supports this.…”
Section: Methodssupporting
confidence: 81%
“…Indeed, recent findings from meta-analyses of genome-wide association studies suggest that even these large-scale efforts so far can only identify variants that together explain 5–15% of the genetic basis of a trait [6], [7], [8], [9]. This suggests that our current analysis approaches and research efforts, including genome-wide association studies, uncover novel genes contributing to disease susceptibility, but still leave large numbers of genes and variants to be uncovered that contribute to the genetic disease risk in the general population [10].…”
Section: Introductionmentioning
confidence: 99%
“…Simulation studies suggested the current method will have limited power when the number of haplotypes increases and the haplotype frequencies are too rare. Among the genes or regions reaching a p-value <10E-4, linkage evidence has been reported in these genes: PLXNA2 (plexin-A2), TRIP13 (thyroid hormone receptor interactor 13), block (42.75-42.76Mb) on chromosome 15, and block (18.259-18.259Mb) on chromosome 20(Lillioja and Wilton 2009). …”
Section: Resultsmentioning
confidence: 99%
“…One could imagine other tiers, dependent upon whether, for example, the variation deleted genes, altered splicing, transcription, or amino acid substitution, or resulted in purely neutral DNA markers [39], [40]. All of these point to an interesting feature of GWAS, that so far they have identified little of the genetic variance for most traits, accounting for amounts of variance and identities of associations that are inconsistent with previous research [41], [42], [43].…”
Section: Introductionmentioning
confidence: 99%